Analysis of consumer preference against handicraft paper from betel nut coir fiber (Areca catechu L.) by using Conjoint method - Dewi, Ika Atsari; Fanani, Muchammad; Deoranto, Panji; Ihwah, Azimmatul; Austria, Cesar Oliver; Risdianto, Hendro; Setyawan, Hendrix Yulis; Wijana, Susinggih; Suryanegara, Lisman; Sarfat, Muhammad Syukur (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
An analysis of consumer preferences to find out the characteristics of handicraft paper from betel nut fiber desired is necessary for this innovation. This study aimed to determine the attributes of handicraft paper that are most necessary for consumers. This study was conducted by using Conjoint method. Fifty respondents completed structured questionnaires in some cities in Indonesia. The attribute mix used in this study was physical and organoleptic. The physical attribute mix was tensile strength, grammage, thickness, and stiffness while the organoleptic was color, fiber appearance, and surface texture. There were 16 combinations of stimuli formed with simplification using orthogonal arrays. The result shows consumers like tensile strength of 20-<30 kN/m2, grammage of ≥500 g/m2, thickness of 1,6-3 mm, stiffness of ≥15 mN.m, dark brown color, the appearance of fiber was visible, and had rough surface texture. The results of the correlation analysis showed that there was a strong correlation between the results of preference stimuli and actual responses. The handicraft paper produced had the same characteristics as the consumer preference, except the tensile strength with thevalue ranged from 10-<20 kN/m2. The results also showed that fiber appearance had the highest relative importance value to be prioritized.